2007
DOI: 10.1007/s00253-007-1016-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of ɛ-caprolactone by overexpression of NADPH-regenerating glucose 6-phosphate dehydrogenase in recombinant Escherichia coli harboring cyclohexanone monooxygenase gene

Abstract: Whole-cell conversion of cyclohexanone to epsilon-caprolactone was attempted by recombinant Escherichia coli BL21(DE3) expressing cyclohexanone monooxygenase (CHMO) of Acinetobacter calcoaceticus NCIMB 9871. High concentrations of cyclohexanone and epsilon-caprolactone reduced CHMO-mediated bioconversion of cyclohexanone to epsilon-caprolactone in the resting recombinant E. coli cells. Metabolically active cells were employed by adopting a fed-batch culture to improve the production of epsilon-caprolactone fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 28 publications
1
64
1
Order By: Relevance
“…14,28,[33][34][35][36][37][38] This growth deficiency has been at least partially alleviated by overexpressing the zwf gene encoding NADP þ -dependent G6P dehydrogenase. 35,38 Increasing Zwf expression and activity additionally increases NADPH regeneration rates during glucose catabolism and has been used to improve NADPH-dependent production of polyhydroxybutyrate (PHB) 39 and e-caprolactone, 40 as well as help relieve the metabolic burden of protein overexpression. 35 The observed increase in Pfk activity and reduction in xylitol yield for strain JC114 compared with JC111, rather than an expected increase in xylitol yield if PPP flux increased, support the possibility that Zwf activity limits PPP flux in this strain (as reported for other strains).…”
Section: Analysis Of Pfk Mutant Resting Cellsmentioning
confidence: 99%
“…14,28,[33][34][35][36][37][38] This growth deficiency has been at least partially alleviated by overexpressing the zwf gene encoding NADP þ -dependent G6P dehydrogenase. 35,38 Increasing Zwf expression and activity additionally increases NADPH regeneration rates during glucose catabolism and has been used to improve NADPH-dependent production of polyhydroxybutyrate (PHB) 39 and e-caprolactone, 40 as well as help relieve the metabolic burden of protein overexpression. 35 The observed increase in Pfk activity and reduction in xylitol yield for strain JC114 compared with JC111, rather than an expected increase in xylitol yield if PPP flux increased, support the possibility that Zwf activity limits PPP flux in this strain (as reported for other strains).…”
Section: Analysis Of Pfk Mutant Resting Cellsmentioning
confidence: 99%
“…1). Strategies such as overexpression of zwf, encoding glucose-6-phosphate dehydrogenase (G6PDH) (Chin et al 2009;Kim et al 2011b;Lee et al 2007), or deletion of pgi, encoding phosphoglucose isomerase (Bartek et al 2010;Chemler et al 2010;Kim et al 2011a), have been used to increase the metabolic flux to PPP from glycolysis. Other strategies include overexpression of pyridine nucleotide transhydrogenase encoded by udhA which converts NADH to NADPH (Sanchez et al 2006), and switching the glycolytic enzyme, NAD + dependent glyceraldehyde-3-phosphate dehydrogenase (GAPDH) to NADP + -dependent GAPDH from Clostridium acetobutylicum (Martinez et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the production of lower ring-sized lactones such as C 6 ε-caprolactone from cyclohexanone by the widely studied Acinetobacter-derived cyclohexanone monooxygenase (CHMO) under nongrowing conditions was found to be about 0.8 g/l/h (Walton and Stewart 2002). Lee et al (2007) reported a 15.3-g/l yield of ε-caprolactone in a glucoselimited fed-batch reaction when glucose-6-phosphate dehydrogenase was co-expressed with CHMO. Perhaps, the best example of a scale-up BV biotransformation came from the strategy of in situ substrate feeding and product removal, known as SFPR (Hilker et al 2004a, b).…”
Section: Discussionmentioning
confidence: 99%